Metaphors in Rentong and Srengenge: An Analysis of Translation Methods and the Transfer of Meaning: (Aspek Metafora dalam Rentong dan Srengenge: Analisis Kaedah Penterjemahan dan Pemindahan Makna) (Jurnal Bahasa, 2015)
This article discusses the transfer of meaning in the translation of metaphors in two Malay novels, namely Rentong and Srengenge, written by Shahnon Ahmad and translated into English by Harry Aveling under the titles Rope of Ash and Srengenge. Metaphors are figures of speech where comparisons are made between two different domains where no similarities exist when examined at surface level. Metaphors are also interrelated with the conceptual system, the value system, the environment and the world view of a particular culture. The differences in these aspects between cultures often pose specific problems in translating metaphors because each culture linguistically manifests their metaphorical thought in a different way. Based on theoretical frameworks of conceptual metaphors by Lakoff and Johnson (1980), meaning-based translation by Larson (1984), loss of meaning in translation by Newmark (1981) and Catford's (1969)notion of untranslatability, this study aims to analyse the metaphor structures found in the above-mentioned novels, identify the method employed by the translator to translate live and dead metaphors from the two literary texts, and finally, seek to examine the transfer of meaning between the source text metaphors and those of the target texts. The findings of the study show that in many cases, the metaphors found in the source text are a) translated according to meaning without keeping the metaphorical structure, or b) translated by preserving the metaphorical expressions of the source text in the target text. The former often causes a certain degree of under translation, while the latter often produces the ideal translation.Keywords: metaphor, meaning-based translation, loss of meaning in translation, untranslatability